FENOMENA KOMUNIKASI LONG DISTANCE MARRIAGE PADA PASANGAN YANG BEKERJA DI UIN MAHMUD YUNUS BATUSANGKAR - Mutiara Lorenza; Mami Nofrianti (KINEMA: Jurnal Komunikasi dan Penyiaran, 2025)
The main problem in this thesis is communication dynamics in Long Distance Marriage among couples employed at UIN Mahmud Yunus Batusangkar, Indonesia, focusing on the processes and management strategies they employ to maintain their relationships. The primary aim is to analyze these interactions and coping mechanisms within this specific context. Employing a qualitative phenomenological approach, the study gathered data through observation, interviews, and documentation from affected couples, followed by analysis involving data collection, reduction, presentation, and verification, with source triangulation ensuring validity. Drawing on DeVito's (2013) interpersonal communication theory, key findings reveal five essential communication processes: leveraging technology, scheduling interactions, fostering transparency and honesty, addressing emotional challenges, and planning physical meetings. Management strategies include discussing conflicts, celebrating significant dates together, sharing nightly stories, setting common goals, and conducting ongoing evaluations and adjustments. However, couples encounter obstacles such as time constraints, communication barriers, and fatigue, alongside broader challenges like achieving work-life balance, providing emotional support, and facilitating career development.